Apios brevis (Fabaceae: Papilionoideae: Phaseoleae), a new species from eastern China - Chen, Yue; Shen, Yun; Wan, Kai-Yuan; Pan, Bo; Jiang, Kai-Wen (Phytotaxa, 2025)
A new species, Apios brevis, is here described and illustrated. This species is currently known only from Qianshan and Yuexi Counties of Anhui Province in eastern China. Phylogenetic analyses based on nuclear ribosomal ITS and chloroplast matK sequences demonstrate that A. brevis is most closely related to A. chindiana and A. fortunei, but it can be readily distinguished from the latter two by its pinnately 3-foliolate leaves, remarkably shorter inflorescences, and smaller flowers. Due to insufficient population data, A. brevis is tentatively assessed as Data Deficient (DD) according to IUCN Red List criteria. An updated key to Apios species is also provided.